ANALYSIS OF TYPES OF LOANS IN TERMS OF INTEREST, TENOR AND CONDITIONS FOR PT. BANK RANKYAT INDONESIA (Persero) Tbk RAMBIPUJI JEMBER UNIT - Suswati; Ahmad Fuji Sugiyarto; Nadia Putri Rahmawati (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Increasing human needs can affect income, if income cannot be met then credit will become a choice for the community, one of which is through banking financial institutions, with the large number of existing banks it can make people confused, therefore before deciding it is very important for people to understand the types of the bank is the destination. This research aims to determine the types of loans in terms of interest, tenor and conditions at PT. Bank Rakyat Indonesia (Persero) Tbk Unit Rambipuji Jember. This research uses descriptive qualitative methods, data collected by observation and interviews. The research results prove that the types of loans in terms of interest, tenor and terms have a positive influence on customer decisions at PT. Bank Rakyat Indonesia (Persero) Tbk Unit Rambipuji Jember.